Analysis of small pelagic fishing grounds using a generalized additive model in the Makassar Strait. Issue 1 (May 2021) - Putri, Rini Sahni; Bibin, Muhammad; Surianti,; Hasrianti,; Damis,; Putri, Andi Rani Sahni; Wulandari, Ully; Wardani, Mentari Puspa
Abstract: Spatial and temporal studies on the distribution of small pelagic fish by applying oceanographic parameters are essential for fisheries management. An understanding of the spatial characteristics of small pelagic fish distributions is important to optimize the sustainability of marine resource utilization. This study examined the characteristics of small pelagic fish fishing grounds through the analysis of oceanographic parameters using remote sensing satellite data and generalized additive model. Remote sensing satellite data (SST and chlorophyll-α) covering the area of Makassar Strait were obtained from NASA databases, with a spatial resolution of 4 km and monthly temporal resolution. Data on the geographical location and catch volume of small pelagic fish were obtained from a fisheries survey in the Makassar Strait. Remote sensing satellite data and fisheries survey data were plotted graphically to determine the environmental conditions at the sites where the small pelagic fish were caught. Catch volume and catch positions were mapped to show fish distribution. The results show that the highest point was around Barru waters with a catch of 30.70kg - 36.75kg. Small pelagic fish were caught in the SST range between 29.82° C - 31.32°C and mostly caught in chlorophyll-a between 0.34 mg/m 3 - 0.62 mg/m 3 .